Psychological differences of patients and relatives - Pérez San Gregorio, María Ángeles; Bernal, José Pérez; Martín Rodríguez, Agustín (The Spanish Journal of Psychology, 2008)
The aim of this investigation is to analyze the psychological differences of patients and their relatives according to the formers’ post-transplantation anxiety. We used two groups of participants: transplant patients (n = 166) and close relatives (n = 166). Four questionnaires were applied: a Psychological Survey (to both groups), the Hospital Anxiety and Depression Scale, and the Quality of Life Questionnaire (to the transplant patients), and the Leeds Scales for the Self Assessment of Anxiety and Depression (to the relatives). Participants were assessed twice: post-Intensive Care Unit (ICU; when patients were moved from the ICU to the Transplantation Unit) and post-hospital (one year after transplant). Results showed that high anxiety in patients just after organ transplant was related to an increase of anxiety and depression symptoms both in patients and relatives one year after transplant; it was also related to a decrease in the quality of life of these patients.